Основні підходи до розуміння сутності феномену перфекціонізму - Фукс, М. А. (ХНУРЕ, 2021)
In most cases, perfectionism can be explained as a wish for everything to be perfect. On the other hand, there have been a lot of debates about the sense of this phenomenon for approximately 60 years already. Therefore, it is discovered to be not a plain belief or conviction. There are plenty of components that may have a tremendous impact on a person, resulting in either healthy perfectionism or maladaptive one. Thus, it is vital to understand the cause of the presence of perfectionism in a person's life to eliminate the consequence of the negative part of this aspect.
Keywords: філософія; перфекціонізм